Pengaruh Lingkungan Kerja Dan Kompensasi terhadap Motivasi Kerja Karyawan J&T Ekspress Cabang Kota Sungai Penuh Selama Pandemi Covid-19 - Fitrina Afrianti (Journal on Education, 2022)
This study aims to identify the effect of the work environment and compensation on the work motivation of J&T Express Sungai Full Branch employees during the Covid-19 Pandemic. This research was conducted to test whether there is a relationship or influence between variables, especially to test the hypothesis in structural equations. The data analysis technique used in this study is the Multiple Linear Regression analysis technique. The results showed that the work environment has a significant effect on work motivation, as evidenced by tcount > ttable, namely 4.130 > 2.03693, and a significance value of 0.041 <0.05. Compensation has a significant effect on work motivation as evidenced by tcount > ttable, namely 3.929 > 2.03693, and a significance value of 0.030 <0.05. Work Environment and Compensation have a significant effect on Work Environment as evidenced by fcount > ftable (6.550 > 3.29) and with a significance value of 0.010 <0.05.